Preoperative ultrasonographic prediction of difficult airway in patients undergoing surgery under general anaesthesia - Sharma, Mona; Dhungel, Saurya; Piya, Buna; Gautam, Ritika (Journal of Kathmandu Medical College, 2022)
Background: Preoperative assessment of the airway with ultrasound has come up as a viable option to aid the preanaesthetic airway assessment. Objectives: To identify reliable ultrasound parameters as predictors of difficult airway in patients undergoing surgery under general anaesthesia. Methods: A prospective analytical cross-sectional study was conducted at Kathmandu Medical College in 99 consecutive patients scheduled for elective surgery with general anaesthesia and endotracheal intubation from July 2019 to June 2020 after ethical clearance. Three ultrasound parameters were used for this study. Distance from the skin to the anterior aspect of trachea at the level of vocal cords (ANS-VC), the depth of the pre-epiglottic space (PreE), the distance from the epiglottis to the midpoint of vocal cords (EVC) was measured. The PreE/EVC and hyomental distance ratio (HMDR), which is the distance ratio of hyomental distance at neutral and extended head position were calculated. These ultrasonographic parameters were used to predict difficult laryngoscopy Cormack-Lehane (CL) grading 3, 4. Results: Difficult intubation was seen in 23 (23.2%) as CL grade 3. The authors did not encounter CL grade 4. HMDR and PreE/EVC have been shown to have significant association with CL grading, with a specificity of 71% and 77% respectively and a high negative predictive value of 84.3% and 84.2% respectively. Therefore, it is valuable in predicting difficult intubation. ANS-VC did not have a significant correlation. Conclusion: Diagnostic predictability of difficult airway is better with HMDR and PreE/E-VC.